Pembentukan Undang-Undang dalam Rangka Pembaharuan Hukum Nasional Di Era Demokrasi - Astomo, Putera (Mahkamah Konstitusi Republik Indonesia, 2014)
On direct democracy era to demand national law reform. That one of part national law reform, that is to form legislation which to regulate whole life levels. If formal and substantial, legislation must be mirror populace aspiration (responsive) until in to form it also to involve active participation from the self populace.